Subacute necrotizing encephalomyelopathy (Leigh syndrome) in pediatric patients: a retrospective study - Tsai, Jeng-Dau; Tsai, Henry J.; Yang, Sheng-Hui; Sheu, Ji-Nan (International Journal of Research in Medical Sciences, 2017)
Background: The clinical manifestations of Leigh Syndrome (LS) are heterogeneous and its diagnosis is often based on information acquired from multiple levels of inquiry. To identify LS, Oral Glucose Lactate Stimulation Test (OGLST) and Magnetic Resonance Spectroscopy (MRS) have been used as additional tools for evaluation of this metabolic disorder. The objective of the study was to report the clinical manifestations, neuroimaging assessments, and multidisciplinary approaches of lactate in pediatric patients with LS. Methods: We performed a retrospective charts review of pediatric patients with LS, which underwent the investigations using laboratory tests and Magnetic Resonance Images (MRI)/MRS of the brain. Results: The distributions of the lesions on the MRI of the brain studies were as the following: basal ganglia (7/8), brainstem (7/8), and cortex (3/8). Despite all of the patients showed disorient neurological manifestations and symmetrical lesions over the basal ganglion and brainstem on MRI, elevated levels of serum lactate were detected in 6 of 8 patients by either random serum sample obtained for lactate or OGLST. Subsequently, the remaining 2 cases were demonstrated with lactate peak over the affected areas by MRS. Cranial MRS showed lactate duplex and decreased N-acetylaspartate/creatine ratio over the affected areas in the 5 of 6 patients. Conclusions: The study shows the importance of multidisciplinary approaches in the diagnosis of LS. Approach of LS may not only depend on the elevation of the value of random serum lactate but also can be further aided by OGLST or MRS to evaluate metabolic disorder in such patients.